Business Processes Mining and Management: An Introduction - Mahapatra (Tapa S) Ed.; Roy (Nivedita) Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2005)
Business Processes Mining
50
Keywords: Business Processes Mining